(untitled) (Journal of the College of Basic Education, 2022)
An experiment was carried out by using plastic pots during growing season 2014 – 2015 in private nursery in Baghdad governorate to study the effect of seeds soaking with Salicylic acid ( SA ) ( 0 , 0.5 , 1 ) mM and salt stress with NaCl ( 0 , 50 , 100 ) mM and their interaction in some growth parameters in Vicia faba L. included : plant height , branches number , pods number , pods length , pods weight , weight of 100 seeds , chlorophyll content , protein percentage and electrolyte leakage in leaf tissues . The experiment designed according to Completely Randomized Design ( CRD ) with three replications . Results showed that salinity stress significant reduction in the averages of growth parameters (plant height , branches number , pods number , pods length , pods weight , weight of 100 seeds , chlorophyll content , protein percentage ) and significant increased in electrolyte leakage , while the seeds soaking with SA caused a significant increase in all the growth parameters and significant reduction in electrolyte leakage . The results showed significant effect of interaction between both factors in all traits .